VILLAGE COMMUNITY EMPOWERMENT IN IMPLEMENTING THE REVITALISATION OF LOCAL CULTURE "CLEAN VILLAGE" - Endrizal; Suharti (EZRA SCIENCE BULLETIN, 2023)
This paper discusses community empowerment in supporting local cultural revitalisation. The purpose of this paper is to see what concrete efforts are made to empower the community of Jorong Balaigurah in implementing the revitalisation of local culture "clean village". This empowerment was carried out in Jorong Balaigurah, Agam Regency, West Sumatra Province. Empowerment time is determined for 3 months, from August to November 2023. To obtain empowerment data, observation, interview, and document- tation techniques were used. As an approach used in this Empowerment is a descriptive approach. The results of the Empowerment show the following. First, concrete efforts to empower village communities in implementing "Clean Village" in Jorong Balaigurah include: first, Community Empowerment Plan, identification of potential Jorong Balaigurah community groups, identification of local wealth, optimal community empowerment efforts, socialisation of empowerment; second Bersih (1) gotong royong (2) Local wisdom values, (3) Cookery, (4) Costs, (5) Revitalisation of Local Culture, concrete efforts to revitalise local culture in implementing "Clean Village" in Jorong Balaigurah is by conducting cultural coaching to young gene- rations with the label regeneration or regeneration of gotong royong culture;